Pengaruh Sumber Daya Manusia, Komitmen Organisasi, Teknologi Informasi Dan Komunikasi Terhadap Penerapan Standar Akuntansi Basis Akrual Di Pemerintah Kota Lhokseumawe - Nur Afni Yunita; Muhammad Yusra; Arliansyah Arliansyah; Nurhasanah Nurhasanah; Kasman Kasman (Department of Management Faculty of Economics and Business, UNIVERSITAS MALIKUSSALEH, 2021)
This study aims to determine the effect of human resources, organizational commitment, information and communication technology on the application of accrual-based accounting standards at the Lhokseumawe City Government. This research uses quantitative methods. The total population of 33 SKPDs in the Lhokseumawe City Government. The sample of this study consisted of 2 respondents from each SKPD, namely the head of finance and employees who operate the SIMDA application as many as 66 respondents. The data was collected by distributing questionnaires with a liker scale measurement. Data analysis in this study using multiple linear analysis. The results of this study indicate that human resources have no effect on the application of accrual-based accounting standards at the Lhokseumawe City Government. Organizational commitment and information technology have an effect on the application of accrual-based accounting standards in the Lhokseumawe City Government. Communication has no effect on the application of accounting standards in the Lhokseumawe City Government.Keywords: Human Resources, Organizational Commitment, Information Technology, Communication, Application of Accrual Basis Accounting Standards